The Catalogue of the Library of Duke Alexander Louis Radziwiłł in Nesvizh (1651) - Witkowski, Rafał (Bibliotheca Lituana, 2012)
The studies on book culture and the functioning of various libraries have been present in academic circle for many decades. For obvious reasons the interest in books among the illustrious members of Radziwiłł magnate family as well as their scope of activity as the patrons of culture have been analyzed by historians. In the context, the history of the famous Radziwiłł library in Nesvizh can be considered as a separate research topic. This magnificent collection was confiscated after the first partition of Polish-Lithuanian Commonwealth (1772) by order of Empress Catherine the Great. Some 15.000 volumes were transported to Saint Petersburg and offered to the Russian Academy of Sciences and Fine Arts (later Russian Academy of Sciences).Nicolas Radziwiłł the Black (1515–1565) is considered to be the founder of the Nesvizh library; however, its full development can be dated back to the time of Nicholas Christopher Radziwiłł “the Orphan” (1549–1616), who rebuilt the ducal palace and organized a library in one of the specially adopted rooms. The Nesvizh collection has been enriched by numerous donations, including that of cardinal and bishop of Vilnius George Radziwiłł (1556–1600), Sigismund Charles Radziwiłł (1591–1642), and many other members ofthe family.The presented catalogue was compiled under the request of Duke Alexander Louis Radziwiłł. This magnate, born in 1594 as a son of Nicolas Christopher Radziwiłł and Elisabeth Eufemia née Wiśniowiecka, received a most privileged education. In 1610 he began his studies in Germany then traveled throughout Germany, France and Italy. He returned to the Polish-Lithuanian Commonwealth by the end of 1620, but in 1624 he left for Italy again, this time in the company of Prince Vladislas Vasa. In summer 1625 he again returned to the Polish-Lithuanian Commonwealth, but soon was totally immersed in political life. Thanks to family connections he advanced his career very fast, becoming in the court marshal of Lithuania in 1635, and grand marshal of Lithuania only two years later. In December 1652 he went to Italy again and died in Bologna March 30, 1654. The manuscript catalogue of the library of Alexander Louis Radziwiłł is currently preserved in the Kórnicka Library of the Polish Academy of Sciences (Ms BK 1320). It contains of two parts. The first of them (f. 1–25r), compiled according to subjects, was written down in April 1651, then second one (f. 26r–46v), compiled alphabetically – in May and June this year. The catalogues are not identical. The first part, divided into classes, is more comprehensive than the second one (alphabetical). The catalogue was composed by John Hanowicz, mayor of Nesvezh. The manuscript has been marked with the ex-libris of the Radziwiłł library (Ex Bibliotheca Radivilliana Ducali Nesvisiensi) and pressmark (Loc. X, No 17). Hanowicz did not state usually the information about the place and year of publication, which makes the precise identification of the books very difficult. Therefore, one can only predict the exact number of the books (and volumes) preserved in the Nesvezh library at that time. It also happened that Hanowicz stated a title of this same book in both versions: once in the original Latin version and then in (abbreviated) Polish form. Among items included the catalogue one can also find manuscripts, maps, drawings and landed estate documents. Most the books were bound with white or red leather, less frequently with green, cherish, orange or red colored leather, and seldom with morocco leather or paper. The bibliographical descriptions provided in the footnotes should be considered only as suggestions, for only direct analysis of a given book (in visu) allows one to identify and link a book with the Radziwiłł Library. Some of the most precious books were kept in the castle treasury. The Nesvizh collections included also musical pieces, e.g. the libretto (?) of the first opera – Il ratto di Helena – performed on September 4th, 1636, in the theater of the lower ducal castle in Vilnius. The music of the famous opera was composed by an anonymous author, but the libretto was produced by Virgilio Puccitelli.The significance of the magnate families (e.g. that of the Radziwiłłs or the Sapiehas) as promoters and patrons of fine arts and literature was enormous and hard to over-estimate in the history of Grand Duchy of Lithuania. A further and detailed study on the content of the Nesvizh library of Duke Alexander Louis Radziwiłł in 1651 gives one the opportunity to present in full and broad contexts a truly European library collection of Baroque culture in the Grand Duchy of Lithuania.
Keywords: none